Exploration of Gel Method For Crystal Growth Media of Functional Coordination Polymers - Yuniar Ponco Prananto; Mohammad Misbah Khunur (Program Pascasarjana Universitas Brawijaya, 2020)
Synthesizing new functional materials, instead of exploring minerals is one way of creating sustainable development and reducing environmental impact due to irresponsible human exploitation on natural resources. For the last few decades, coordination polymers (CPs) have been emerge as new functional materials with promising features, such as porosity, magnetism, and catalytic activity, CPs have been developed for gas storage, adsorbents, catalysts, magnetic materials, etc. Some common synthetic methods to prepare CPs includes solvo-thermal, bench-top, and melting method. These methods sometimes are unique and the only option to get the targeted CPs. Meanwhile, gel method has been extensively used to grow various crystalline organic and inorganic materials and yet less explored for obtaining CPs. Based on literature review, with some examples from our previous research, this paper is exploring the potential used of gel method for growing crystalline functional CPs, their limitation, as well as advantages and disadvantages. General information about CPs and gel techniques are also presented. Upon discussion, although this method is not the most favourable techniques at this stage, it is suggested that incorporating gel method for growing crystalline functional CPs might be useful and in some cases crucial, especially for low-water soluble inorganic materials.